Phantom Writing - Michael Hirschbichler (Footprint)
In this visual essay I present a body of artistic work done within informal urban and suburban heritage sites in Kyoto. Through the media of text, photography, film and site-specific painting, my works from the cycle Spirit Grounds engage with these sites involving material physical aspects as well as beliefs, fictions, and more-than-human beings. Building upon this, I propose ‘phantom writing’ or ‘phantasmography’ as a situated, multidisciplinary and multisensory approach aimed at understanding and designing contemporary places, landscapes and environments, acknowledging and mediating the agency of diverse phantoms and phantasms.